Effect of Pore Size on the Biodegradation Rate of Silk Fibroin Scaffolds - Zuwei Luo; Qin Zhang; Meijing Shi; Yang Zhang; Wei Tao; Mingzhong Li (Advances in Materials Science and Engineering)
Controlling the degradation rate of silk fibroin-based biomaterial is an important capability for the fabrication of silk-based tissue engineering scaffolds. In this study, scaffolds with different pore sizes were prepared by controlling the freezing temperature and the silk fibroin concentration. In vitro degradation results showed that the internal pore walls of the scaffolds with a larger pore size collapsed upon exposure to collagenase IA for times ranging from 6 to 12 days, and the silk scaffolds exhibited a faster rate of weight loss. The morphological and structural features of the silk scaffolds with a smaller pore size maintained structural integrity after incubation in the protease solution for 18 days, and the rate of weight loss was relatively slow. Scaffolds with a smaller pore size or a higher pore density degraded more slowly than scaffolds with a larger pore size or lower pore density. These results demonstrate that the pore size of silk biomaterials is crucial in controlling the degradation rate of tissue engineering scaffolds.